Development and validation of the supervision practice in human services scale. (25th April 2022) - Osteen, Philip J.; King, Erin A.; Wilke, Dina
Abstract: This paper reports on the development and validation of a scale to measure supervision practice in human service agencies. Supervision in human services is designed to provide management, mediation, professional development, and personal support to workers. The Supervision Practices in Human Services scale (SPHS) captures a range of supervisory practices from productive to abusive behaviours. The SPHS had strong psychometric properties. It includes 23 items with four subscales (Leadership, Inattention, Unprofessional Modelling, Unethical Practice). The SPHS can be used to identify training needs for supervisors or identify where interventions are needed to stop harmful behaviour.